Water-soluble zinc-based battery with hydroxyl-rich hydrogel electrolyte
The hydroxyl-rich hydrogel electrolyte in RAZBs addresses the limitations of PBA cathodes by enhancing ion desolvation and diffusion, achieving high capacity and stability, enabling long cycle life and wide temperature operation.
Patent Information
- Application Number
- CN202310740791.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
Rechargeable aqueous zinc batteries (RAZBs) face limitations due to the small specific capacity and short lifespan of Prussian blue analogs (PBA) cathodes, attributed to incomplete redox site activation, dissolution in aqueous electrolytes, and instability of the crystal structure, which hinders their viability.
A hydroxyl-rich hydrogel electrolyte is introduced, comprising a cathode, anode, and a hydroxyl-rich hydrogel electrolyte with specific components, enhancing ion desolvation and diffusion, and providing an extended electrochemical stability window, thereby activating more redox sites and stabilizing the PBA cathode.
The hydroxyl-rich hydrogel electrolyte enables high-capacity, stable voltage platforms and extended cycle stability, allowing the battery to operate stably for over 10,000 cycles with a capacity retention rate of at least 75%, and supports high energy density and wide temperature operation.
Smart Images

Figure CN119181869A_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to developing and improving battery systems, including the design, assembly and performance optimization of batteries. Background Art
[0002] Faced with the increasing market demand for energy storage, rechargeable aqueous zinc batteries (RAZBs) have become the focus of research in recent years. Aqueous zinc batteries have become an alternative due to their advantages such as high cost-effectiveness, intrinsic safety, high ionic conductivity and simple process. Prussian blue analogs (PBA) are suitable cathode materials for RAZBs due to their high potential. However, their specific capacity is small (<70 mAh g) due to limited redox sites and dissolution in aqueous electrolytes. -1 ), slowing down their viability development.
[0003] Previous studies have shown that carbon-coordinated iron in Prussian blue analogs can be activated by high voltage scanning to achieve relatively stable Zn||PBA batteries. 1 However, the low discharge platform (<1.5 V) and the high cost of using high concentration salts limit the practical application of this approach. In other studies, the phase transition of Prussian blue analog cathodes enables Zn||PBA batteries to achieve high discharge platforms (>1.5 V) and high specific capacities (about 100 mAh g -1 ), but these batteries have a short lifespan (<1000 cycles) due to the dissolution of the PBA cathode and the difficulty of desolvation during cycling. These limitations can be attributed to the incomplete activation of redox sites during metal ion insertion / deinsertion and the instability of the crystal structure.
[0004] Considering these limitations, it is crucial to develop an affordable electrolyte with an extended electrochemical stability window (ESW), easy desolvation, and suppressed dissolution of Prussian blue analogs in aqueous electrolytes. Summary of the invention
[0005] The purpose of the present invention is to provide a water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte. The provided hydrogel electrolyte provides a new possibility for fully activating the reaction sites of PBA and enhancing the desolvation and diffusion of ions in PBA, thereby achieving high capacity, high stable voltage platform and excellent cycle stability. This achievement provides a new opportunity for the application of PBA.
[0006] In one aspect, the present invention provides a water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte, comprising a cathode, an anode, and a hydroxyl-rich hydrogel electrolyte. The cathode has a current collector and at least one active material, wherein the at least one active material is K x Fe y Mn1-y [Fe(CN)6] w ·zH2O, where 0 <x,y,w<1,z> 0. The hydrogel electrolyte material includes a salt solution electrolyte, at least one organic solvent, polyacrylamide and D(+)-glucose monohydrate. When the current density is between 1.0A g -1 Up to 4.0A g -1 The water-soluble zinc-based battery with the hydroxyl-rich hydrogel electrolyte can stably operate for at least 10,000 cycles at 0.2 mA cm -2 and an area capacity of 0.2 mAh cm -2 It has a cycle life of more than 1400 hours under the conditions of , and achieves a high capacity retention rate of at least 75%.
[0007] According to one aspect of the present invention, the water-soluble zinc-based battery further includes a separator between the cathode and the anode.
[0008] According to one aspect of the present invention, the material of the anode includes a zinc plate or a zinc foil.
[0009] According to one aspect of the present invention, the current collector includes carbon cloth, carbon paper, graphite paper, titanium foil / mesh, or stainless steel.
[0010] According to one aspect of the present invention, the volume percentage of the at least one organic solvent is between 0.1% and 70%, and the organic solvent comprises one or more selected from methanol, ethanol, ethylene glycol, glycerol and butene tetraol.
[0011] According to another aspect of the present invention, the cathode further comprises one or more conductive particles and at least one binder. The one or more conductive particles comprise conductive carbon black and Ketjen black, and the binder comprises polyvinylidene fluoride and polytetrafluoroethylene.
[0012] According to one aspect of the present invention, the salt solution electrolyte includes potassium salt and zinc salt.
[0013] According to one aspect of the present invention, the at least one hydrogel electrolyte is prepared by the following method: preparing the salt solution electrolyte at room temperature and pressure; mixing the organic solvent with the salt solution electrolyte to form a first mixed solution; dissolving the polyacrylamide, the D(+)-glucose monohydrate and a photoinitiator in the first mixed solution to form a second mixed solution, wherein the molar ratio of the polyacrylamide to the D(+)-glucose monohydrate is 7:1; transferring the second mixed solution to a mold and exposing it to UV for reaction and bubbling the second mixed solution with an inert gas to remove oxygen to form a hydrogel electrolyte rich in hydroxyl groups.
[0014] According to one aspect of the present invention, the inert gas includes nitrogen and argon.
[0015] According to one aspect of the present invention, the time of exposure to UV for reaction is 30 to 180 minutes.
[0016] The present invention has the following advantages: (1) The preparation process of hydroxyl-rich hydrogel electrolyte is simple, the raw material price is low, the reaction process is safe and environmentally friendly, and it has the potential for large-scale production; (2) The prepared hydroxyl-rich hydrogel electrolyte has an extended electrochemical stability window and the characteristics of easy desolvation of zinc ions. At the same time, based on the large number of hydroxyl groups on the polymer chain, a complete phase transition of the PBA cathode material is achieved, paving the way for obtaining a high discharge platform and high-capacity water-soluble zinc-ion battery; (3) The prepared hydroxyl-rich hydrogel electrolyte has strong adhesion, which helps to achieve long-life Zn||PBA batteries; (4) The hydroxyl-rich hydrogel electrolyte has excellent resistance to high and low temperatures, so the prepared aqueous zinc-based battery can operate in a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention will be more readily understood from the following description of exemplary embodiments with reference to the accompanying drawings, in which:
[0018] Figure 1 A schematic diagram of the synthesis of a hydroxyl-rich hydrogel according to one embodiment of the present invention is depicted.
[0019] Figure 2 ATR-FTIR curves of hydroxyl-rich hydrogel electrolytes with different EG contents are depicted.
[0020] Figure 3 A schematic diagram depicting the state of water molecules in a hydrogel electrolyte according to one embodiment of the present invention is shown.
[0021] Figure 4A depicts the ATR-FTIR spectra of 40% EG PAM@DM hydrogel and 40% EG solution electrolyte according to one embodiment of the present invention; Figure 4B Raman spectra of 40% EG PAM@DM hydrogel and 40% EG solution electrolyte are depicted; Figure 4C Raman spectra of 40% EG PAM@DM hydrogel and 40% EG solution electrolyte are depicted; Figure 4D Depicted are the DSC graphs of 40% EG PAM@DM and PAM hydrogel electrolytes.
[0022] Figure 5Depicted are LSV curves of hydrogel and solution electrolytes at 5 mV / s according to one embodiment of the present invention.
[0023] Figure 6 The cycling performance of a Zn||KFeMnHCF battery assembled with a 40% EG solution electrolyte according to one embodiment of the present invention is depicted.
[0024] Fig. 7A The charge and discharge curves of 40% EG PAM@DM battery are depicted (scanning voltage: 0.6-2.0 V); Figure 7B The charge and discharge curves of 40% EG PAM@DM battery (scanning voltage: 0.6-2.3 V) are depicted.
[0025] Fig. 8A The charge-discharge curves of Zn||KFeMnHCF full cells (denoted as 40% EG PAM@DM cells) assembled with 40% EG PAM@DM hydrogel electrolyte and the energy density at 2.0 and 2.3 V cutoff voltages are depicted. Figure 8B The corresponding cycling performances of 40% EG PAM@DM cells at voltages of 0.6–2.3 V and 0.6–2.0 V are depicted.
[0026] Fig. 9 In situ CV curves recorded at 5 mV / s are depicted.
[0027] Fig. 10A Depicts the XRD patterns of the KFeMnHCF electrode of the Zn||KFeMnHCF battery using a hydroxyl-rich hydrogel electrolyte at different cycle times; Fig. 10B Depicted are the ICP results of the KFeMnHCF cathode obtained after cycling; Fig. 10C Depicted are the Mn 2p XPS results of the KFeMnHCF cathode obtained after cycling; Fig. 10D Depicted is the ex situ XPS spectrum of C1s of the KFeMnHCF cathode obtained after cycling.
[0028] Fig.11A Depicts the cycling performance of a zinc symmetric battery using a 40% EG PAM@DM hydrogel electrolyte according to one embodiment of the present invention. The inset is an optical image of the zinc foil after 80 hours of cycling; Fig. 11B Depicted is the cycling performance of a zinc symmetric cell using a 40% EG solution electrolyte. The inset is an optical image of the zinc foil after 80 hours of cycling.
[0029] Fig. 12A The cycling performance of Zn||KFeMnHCF batteries assembled with hydroxyl-rich hydrogel electrolyte with 0% EG content (0% EG PAM@DM) is depicted. Fig. 12B The cycling performance of Zn||KFeMnHCF batteries assembled with hydroxyl-rich hydrogel electrolyte containing 15% EG (15% EG PAM@DM) is depicted. Fig. 12C The cycling performance of Zn||KFeMnHCF batteries assembled with hydroxyl-rich hydrogel electrolyte containing 30% EG (30% EG PAM@DM) is depicted. Fig.12D The cycling performance of Zn||KFeMnHCF cells assembled with 60% EG-content hydroxyl-rich hydrogel electrolyte (60% EGPAM@DM) is depicted.
[0030] Fig.13A Depicted at 1.5Ag -1 Long cycle performance of 40% EG PAM@DM; Fig. 13B Depicted at 2.66A g -1 Long cycle performance of 40% EG PAM@DM; Fig. 13C The cycling performance of Zn||KFeMnHCF batteries assembled with 40% EG PAM@DM hydrogel electrolyte is depicted.
[0031] Fig.14A The cycling stability and capacity comparison of the KFeMnHCF cathode of the present invention and the PBA cathode on the market in aqueous RAZB are depicted; Fig. 14B Depicted in the range of 1.87-3.74A g -1 The rate capability at various current densities; Fig. 14C Depicted in the range of 1.87-3.74A g -1 The corresponding GCD spectra at various current densities.
[0032] Fig.15 The subsequent cycling performance of the 40% EG PAM@DM battery after 80 cycles is depicted.
[0033] Fig.16 The 40% EG PAM@DM battery according to one embodiment of the present invention is shown in FIG. -1 The magnification performance.
[0034] Fig.17 The rate performance comparison of the KFeMnHCF cathode of the present invention and the commercially available PBA cathode in aqueous RAZB is depicted.
[0035] Fig.18 Depicted is a graph of a 3 mA cm -2 and the cathode loading mass is about 26 mg cm -2 Cycling performance of 40% EG PAM@DM battery.
[0036] Fig.19A Depicted is a diagram of a loading mass of 1 mg cm according to one embodiment of the present invention. -2 , current density is 0.3Ag -1 The charge and discharge curves at Fig.19B The loading mass is 1 mg cm -2 , current density is 0.3A g -1 Cycle performance when Fig.19C The loading mass is depicted as 8 mg cm -2 , current density is 0.3 mA cm -2 The charge and discharge curves at Fig.19D The loading mass is depicted as 8 mg cm -2 , current density is 0.3 mA cm -2 Cycle performance.
[0037] Fig. 20A A photograph of a hydroxyl-rich hydrogel is shown; Fig. 20B Schematic diagram showing the strong adhesion of hydroxyl-rich hydrogels to substrates.
[0038] Fig.21A Optical photographs of the cathode electrode before and after cycling are shown; Fig. 21B Depicted are the ICP results of the 40% EGPAM@DM cathode electrode after the 50th cycle; Fig. 21C The ICP results of the cathode electrode of 40% EG solution after the 50th cycle are depicted; Fig.21D The KFeMnHCF electrode (40% EG solution) at 1.5 A g -1 XRD pattern of the 50th cycle at the current density; Fig.21E The KFeMnHCF electrode (40% EG PAM@DM) at 1.5 A g -1 XRD pattern of the 50th cycle at the current density. In the figure, C represents charging and D represents discharging; Fig.21F Depicted are the Raman spectra of the FKFeMnHCF electrode before and after cycling.
[0039] Fig.22A Schematic diagram showing the operation of 40% EG PAM@DM in a wide temperature range; Fig. 22B Optical images of PAM and 40% EG PAM@DM hydrogels at -20 °C are shown; Fig. 22C The mass loss curves of 40% EG PAM@DM and PAM hydrogels at room temperature (about 30 °C and 23% humidity) for 7 days are depicted; Fig.22D The charge and discharge curves of 40% EG PAM@DM battery at 50 °C are depicted; Fig.22EThe charge and discharge curves of 40% EG PAM@DM battery at 25°C are depicted; Fig.22F The charge and discharge curves of 40% EG PAM@DM battery at -20°C are depicted; Figure 22G The cycling performance of 40% EG PAM@DM cells at 50 °C is depicted. DETAILED DESCRIPTION
[0040] In the following description, a hydroxyl-rich hydrogel electrolyte and a zinc-based battery containing the same will be exemplified. For those skilled in the art, even if modifications, additions and / or substitutions are made, they will not deviate from the scope and spirit of the present invention, and therefore the scope of the present invention is not limited thereto. Specific details may be omitted to avoid obscuring the invention; however, the present disclosure is written to enable professionals familiar with the present technology to implement the technology disclosed in the present disclosure without excessive experiments.
[0041] Aqueous zinc-based batteries have the advantages of high safety, environmental friendliness, and low cost. Directly using zinc foil as anode material is one of the most promising large-scale energy storage battery technologies. At present, the metal zinc anode is the key to restricting the practical application of aqueous zinc-based batteries, mainly manifested in the bottlenecks of zinc dendrite growth, severe volume change, hydrogen evolution corrosion reaction, and poor electrode reversibility, limited cycle life, and low coulombic efficiency caused by the above problems. In addition, the typical state of PBA cathode materials in ordinary electrolytes: dissolved, non-reactive high-spin Fe sites and large solvation energy lead to poor performance.
[0042] Therefore, the present invention provides a preferred electrolyte that can activate high-spin Fe, prevent dissolution and reduce solvation energy to obtain high performance. The hydroxyl-rich hydrogel electrolyte shows an extended electrochemical stability window (ESW), easy desolvation and strong adhesion to aqueous zinc||Prussian blue derivative (Zn||PBA) batteries. The use of hydroxyl-rich hydrogel electrolytes and extending their electrochemical stability windows (ESWs) helps to activate the redox sites of low-spin iron in the PBA cathode while regulating its crystal structure. Having an extended electrochemical stability window (ESW) allows high voltage scanning to activate more reaction sites. The phase change of PBA may help to achieve a high discharge platform and a large specific capacity. In addition, the hydroxyl-rich hydrogel electrolyte has good adhesion and prolongs the life of zinc-potassium batteries by delaying the dissolution of the cathode material and preventing the material from falling off.
[0043] According to another aspect of the present invention, the hydroxyl-rich hydrogel electrolyte can be applied to a water-soluble Zn||PBA battery. The battery includes a cathode, an anode, and a hydroxyl-rich hydrogel electrolyte, which provides a channel for ion conduction between the cathode and the anode. During the charging process, an external power source injects electrons into the zinc anode to oxidize zinc to Zn2+ ions, while the PBA analog KFeMnHCF cathode absorbs potassium ions. When the stored energy needs to be released, the zinc anode releases Zn 2+ ions, and at the same time, the PBA cathode releases potassium ions and electrons, thereby generating current to supply the external load.
[0044] In one embodiment, the water-soluble Zn||PBA battery of the present invention is a diaphragm-free battery. The hydroxyl-rich hydrogel electrolyte can simultaneously replace the separator between the cathode and the anode to prevent short circuit between the anode and the cathode. Diaphragm-free batteries can use internal space more efficiently and provide higher energy density. This means that they can store more energy, making the battery more superior in terms of volume and weight. In addition, since there is no separator, the internal impedance is relatively low, thereby improving energy output and charging efficiency.
[0045] In one embodiment, the cathode has a current collector and at least one active material. The at least one active material is K x Fe y Mn 1-y [Fe(CN)6] w ·zH2O, where 0 <x,y,w<1,z> 0. The current collector includes, but is not limited to, carbon cloth, carbon paper, graphite paper, titanium foil / net, or stainless steel. The material of the anode includes, but is not limited to, zinc plate or zinc foil.
[0046] In one embodiment, the salt solution electrolyte includes potassium salt and zinc salt, the potassium salt includes but is not limited to one or more of potassium bis(trifluoromethanesulfonyl)imide, potassium trifluoromethanesulfonate, potassium perchlorate, potassium borofluoride, potassium chloride, and potassium sulfate, and the zinc salt includes but is not limited to one or more of zinc trifluoromethanesulfonylimide, zinc perchlorate, zinc borofluoride, zinc chloride, and zinc sulfate.
[0047] In another embodiment, the cathode may further include one or more conductive particles and at least one binder, wherein the one or more conductive particles include conductive carbon black and Ketjen black, and the binder includes polyvinylidene fluoride and polytetrafluoroethylene.
[0048] The material of the hydroxyl-rich hydrogel electrolyte includes a salt solution electrolyte, at least one organic solvent, polyacrylamide and D(+)-glucose monohydrate (DM), and the organic solvent and DM are both sources of hydroxyl groups. The volume percentage of at least one organic solvent is between 0.1% and 70%, including but not limited to methanol, ethanol, ethylene glycol, glycerol and butene tetraol. The hydroxyl-rich hydrogel electrolyte is prepared by the following method: Prepare salt solution electrolyte at normal temperature and pressure; mixing an organic solvent with a salt solution electrolyte to form a first mixed solution; Dissolving polyacrylamide, D(+)-glucose monohydrate and a photoinitiator in the first mixed solution to form a second mixed solution; The second mixed solution is transferred into a mold and exposed to UV for reaction and an inert gas is bubbled through the second mixed solution to remove oxygen, thereby forming a hydrogel electrolyte having rich hydroxyl groups.
[0049] In one embodiment, a mixed solution of potassium salt and zinc salt or a combination thereof is used as the electrolyte of the salt solution. Potassium salts include but are not limited to one or more of fluorotrifluoromethanesulfonylmethylenetoluene, potassium trifluoromethanesulfonate, potassium perchlorate, potassium borofluoride, potassium chloride, and potassium sulfate; zinc salts include but are not limited to one or more of trifluoromethanesulfonylmethylenetoluene zinc, trifluoromethanesulfonate methylenetoluene zinc, zinc perchlorate, borofluoride zinc, zinc chloride, and zinc sulfate.
[0050] In a preferred embodiment, a mixed solution of potassium trifluoromethanesulfonate (KSO3CF3) and zinc trifluoromethanesulfonate (Zn(SO3CF3)2) is used as the salt solution electrolyte. The mixed volume ratio is between 1:1.
[0051] In one embodiment, the molar ratio of the polyacrylamide to the D(+)-glucose monohydrate is 7:1.
[0052] In one embodiment, the photoinitiator may be any photoinitiator available on the market.
[0053] In a preferred embodiment, the organic solvent is ethylene glycol (EG), and the volume percentage is between 0.1% and 70%. For example, the volume percentage is 0%, 15%, 30%, 40%, 60%. More preferably, the volume percentage of ethylene glycol (EG) is 40%.
[0054] The current density is between 1.0A g -1 Up to 4.0A g -1 When the hydroxyl-rich hydrogel electrolyte is used, the Zn||PBA battery stably operates for at least 10,000 cycles, has a cycle life of more than 1400 hours, and achieves a high capacity retention rate of at least 75%.
[0055] In a preferred embodiment, the Zn||PBA battery with hydroxyl-rich hydrogel electrolyte is -1 It can operate stably for at least 14,500 cycles under the same conditions, with a discharge platform up to 1.7V and a capacity of at least 100mAh g -1 In addition, the loading mass of PBA in the hydroxyl-rich hydrogel electrolyte is as high as 26 mg cm -2 , and contributed about 1.8 mAh cm -2At extremely low current density (0.3 mA cm -2 ), the battery achieves a high discharge platform (about 1.9V) and a large specific capacity (about 160mAh g -1 ).
[0056] Example
[0057] Example 1
[0058] Material
[0059] Acrylamide (PAM), D(+)-glucose monohydrate (DM), photoinitiator 2959 (IRGACURE2959), ethylene glycol (EG), potassium trifluoromethanesulfonate (KSO3CF3) and zinc trifluoromethanesulfonate (Zn(SO3CF3)2) were purchased from Aladdin and used directly without further purification. Potassium tetracyanoferrous trihydrate (K4Fe(CN)6·3H2O), potassium chloride (KCl), ferrous sulfate heptahydrate (FeSO4·7H2O) and manganese sulfate monohydrate (MnSO4·H2O) were purchased from MACKLIN and used directly. Deionized (DI) water was used in all experiments.
[0060] Example 2
[0061] Synthesis of hydroxyl-rich hydrogels
[0062] Hydroxyl-rich hydrogel electrolytes were prepared by atom-radical polymerization methods, such as Figure 1 As shown. 0.07 mol of PAM, 0.01 mol of DM and 0.1 g of photoinitiator IRGACURE 2959 were dissolved in 20 ml of a mixed solution containing 40% ethylene glycol (EG) and 60% of 1M KSO3CF3 and 1M Zn(SO3CF3)2 (volume ratio, expressed as 40% EG solution). After stirring the mixture for 10 minutes, it was transferred to a custom mold and exposed to UV light (365 nm, 15 watts) for 40 minutes. The resulting mixture was bubbled with nitrogen to remove oxygen, thereby synthesizing a hydroxyl-rich hydrogel electrolyte (expressed as 40% EG PAM@DM). Both ethylene glycol solution and DM are sources of hydroxyl groups.
[0063] The mass percentage composition of the 40% EG PAM@DM hydrogel electrolyte (calculated based on the charge ratio) is 19% by weight of KSO3CF3 and Zn(SO3CF3)2, 20% by weight of polymer, 0.26% by weight of ethylene glycol (EG), and 35% by weight of water (H2O). The water content is calculated as follows: Water content (weight percentage concentration) = {12 / [(0.07*71.1+0.01*198.2)+12+8*1.1132+0.012*(363.53+188.17)]}*100%≈35%, (The relative molecular masses of KSO3CF3 and Zn(SO3CF3)2 are 188.17 and 363.53 respectively.)
[0064] In one embodiment, the same method was used to prepare hydroxyl-rich hydrogel electrolytes with different EG contents, with volume ratios of 0%, 15%, 30%, and 60%, respectively, denoted as 0% EG PAM@DM, 15% EG PAM@DM, 30% EG PAM@DM, and 60% EG PAM@DM hydrogels.
[0065] Characterization of hydroxyl-rich hydrogels
[0066] Fourier transform infrared spectroscopy (FTIR, PerkinElmer) and Raman spectroscopy (WITec RAMANalpha300R) were used to investigate the structural characteristics of the hydrogels. Figure 2 The results showed that 1455 and 1320 cm -1 The signal peaks at 1640 and 1074 cm -1 The peak at is attributed to DM. In the prepared hydrogel, two different water molecules surround the hydrophilic functional groups on the polymer chain ( Figure 3 ). In the designed hydrogels, the enhanced bound water molecules and reduced free water molecules can be identified by the changes in hydrogen bond strength. Figure 4A ATR-FTIR spectra of 40% EGPAM@DM hydrogel electrolyte and 40% EG solution electrolyte are shown. After adding PAM@DM hydrogel, the hydroxyl stretching (3,200-3,400 cm) of H2O in 40% EG solution -1 ) and bending (1640cm -1 ) moves to a higher wavelength, i.e. from 3305cm -1 To 3363cm -1 and from 1640cm -1 To 1664cm -1 . Figure 4A 3210cm -1 and 1602cm -1 The signal peaks are attributed to the stretching and bending peaks of HO(DM).
[0067] Raman spectroscopy (WITec RAMAN alpha 300R) was used to study the state of water molecules in the hydrogel, including the stretching and bending modes of -OH, and the relative number of water molecules in different states. As shown in FIG.4B, the vibrations of strong hydrogen bonds in tetrahedral coordination and weak hydrogen bonds in incomplete tetrahedral structures are concentrated at 3242 cm -1 and 3422cm -1 These two signal peaks are called “ice-like” and “liquid-like” modes. In 40% EG PAM@DM hydrogel, I 3242 / I 3422 The ratio (0.95) is higher than that of the 40% EG solution electrolyte (0.83), indicating that more "ice-like" hydrogen bonds are formed in the hydrogel electrolyte. This is due to the incorporation of a large amount of -OH, which significantly enhances the hydrogen bonding interaction between the hydrogel and water molecules. In addition, in the 40% EG PAM@DM, the 1664 cm -1 The HO bending mode at 1625 cm-1 in 40% EG solution is -1 The bending mode is more obvious at Figure 4C ), indicating a stronger interaction. Figure 4C 1602cm -1 The peak is the HO(DM) bending mode.
[0068] Differential scanning calorimetry (DSC, Mettler DSC3+) is an established method to distinguish the state of water in hydrogels. Differential scanning calorimetry was used to study the enthalpy change during phase change. PAM hydrogel electrolyte was selected as a control for comparison. The data results clearly show that the sharp peak at about -25°C is the freezing point of water in 40% EG PAM@DM ( Figure 4D ), in PAM hydrogel, the broad peak at about 0°C is the freezing point of water. The above results indicate that the interaction between polymer chains and water molecules in EG PAM@DM hydrogel is stronger than that in PAM hydrogel.
[0069] In addition, the present invention also uses X-ray diffraction (XRD, D2 PHASER) to record the pattern to determine the crystal structure of the particles. Inductively coupled plasma optical emission spectrometry (ICP-OES, Agilent) is performed to detect the element content. Finally, X-ray photoelectron spectroscopy (XPS, Thermo Fisher Scientific K-Alpha) is used to determine the binding energy of the elements during the cycle.
[0070] The synthesized hydroxyl-rich hydrogels exhibited more bound water molecules and reduced free water molecules, allowing for an extended electrochemical stability window (ESW). Linear sweep voltammetry (LSV) was performed at a scan rate of 5 mV / s to explore the ESW of these hydrogel electrolytes and 40% EG solution, and the results are shown in Figure 5 middle. Figure 5 The middle inset provides a magnified view of the region near the cathode limit. The results show that the ESW of the hydroxyl-rich hydrogel electrolyte is much larger than that of the 40% EG solution electrolyte (~2.4 V), ranging from 3.0 to 3.2 V. Among all the hydroxyl-rich hydrogel electrolytes tested, the 40% EG PAM@DM hydrogel electrolyte shows the widest ESW of about 3.2 V.
[0071] Example 3
[0072] Preparation of KFeMnHCF cathode
[0073] K x Fe y Mn 1-y [Fe(CN)6] w ·zH2O(0 <x,y,w<1,z> 0) The cathode was manufactured as follows: First, 6.5 mmol of MnSO4·H2O and 1.5 mmol of FeSO4·7H2O were dissolved in 100 ml of saturated KCl solution, while 2 mmol of K4Fe(CN)6·3H2O was dissolved in 80 ml of saturated KCl solution. The mixture of MnSO4·H2O and FeSO4·7H2O was slowly added to the K4Fe(CN)6·3H2O solution stirred magnetically at 60°C. The reaction was allowed to proceed for 12 hours, and then the mixture was centrifuged and washed several times with deionized water. After the sample was dried in an oven at 80°C for 12 hours, a dark green product was obtained.
[0074] To prepare the KFeMnHCF cathode, KFeMnHCF powder, Ketjenblack (Sigma), and polyvinylidene fluoride (PVDF, Sigma) were thoroughly mixed and ground in a mass ratio of 7:2:1. N-Methylpyrrolidone (NMP, Aladdin) was added to the mixture as a solvent and stirred to obtain a uniform slurry. The resulting slurry was carefully coated on a titanium mesh (Ti) and dried in a vacuum oven at 60°C for 4 hours to produce the KFeMnHCF cathode.
[0075] Example 4
[0076] Preparation of Zn || KFeMnHCF battery
[0077] The expanded ESW of the hydroxyl-rich hydrogel endows Zn / K batteries with high voltage sweep potential. To test this, a pouch cell was assembled in this example using K x Fe y Mn 1-y [Fe(CN)6] w · Aqueous Zn||KFeMnHCF batteries were assembled using zH2O(KFeMnHCF) as anode, combined with different hydroxyl-rich hydrogels or 40% EG solution as electrolyte, and zinc foil as cathode. The prepared Zn||KFeMnHCF batteries exhibited high energy density, stable multiple output potentials, and good cycling stability in hydrogel electrolytes, showing superior energy storage prospects in high energy density and high power batteries.
[0078] Example 5
[0079] Electrochemical test results
[0080] Figure 6 The cycling performance of the 40% EG solution battery was recorded. Due to the high voltage scan (scan voltage of 0.6-2.3 V), a relatively high specific capacity of about 100 mAh g -1 However, after 100 cycles, the battery failed quickly with a low coulombic efficiency (about 80%), which was caused by the narrow ESW of the 40% EG solution electrolyte and the difficulty of desolvation. In contrast, low-voltage scanning (0.6-2.0 V) can only achieve a lower specific capacity of less than 50 mAh g -1 .
[0081] In order to study the cycling performance of the battery based on 40% EG PAM@DM, tests at different sweep voltages were also carried out. Fig. 7A As shown, when the scan voltage is in the range of 0.6-2.0V, at 1.5Ag -1 A relatively low discharge plateau (about 1.6 V) and a rather low discharge specific capacity (less than 50 mAh g -1 ). However, when the scan voltage was increased to 2.3 V, a significant improvement in the battery performance was observed. Specifically, at 1.5 A g -1 A discharge platform of about 1.7V and a capacity of more than 100mAh g -1 The discharge capacity ( Figure 7B ). Even if the current density is increased to 1.87A -1 The discharge platform, specific capacity and energy density of the high-voltage scanning battery are also about three times that of the low-voltage scanning battery ( Fig. 8A ). It is noteworthy that the difference in electrochemical behavior between high-voltage scans and low-voltage scans remains consistent throughout the entire cycling process ( Figure 8B ).
[0082] exist Figure 7B The characteristics of the current-voltage curve evolve slowly during the rest of the electrochemical process. The two high discharge plateaus in the curve merge into one plateau after 50 cycles, when the discharge capacity drops to about 120 mAh g -1 . This can be attributed to the transformation of the cathode structure to a highly stable state that optimizes the rapid insertion / extraction of metal ions, for example, from KFeMnHCF to KFeZnHCF. The activation of low-spin Fe(III) coordinated to the carbon of the cyano group in the KFeMnHCF cathode is another factor contributing to the advantage in high-voltage scanning performance. This activation leads to a high discharge plateau of 1.61 V. The discharge plateau of 1.15 V belongs to the high-spin Fe(III) coordinated to the nitrogen of the cyano group in the KFeMnHCF cathode.
[0083] Reference Fig. 9 , it can be observed that in the first 52 cycles, the cathode peak contribution of 1.15V decreases rapidly and disappears during this period; while the cathode peak of 1.61V gradually increases. The present invention also uses an electrochemical workstation (CHI 760e) to perform in-situ cyclic voltammetry (CV) to record the electrochemical behavior of multiple redox sites undergoing high voltage scanning. The cathode peaks at 1.61V and 1.15V are respectively determined to be the reduction peaks of low-spin and high-spin Fe (III) and carbon and nitrogen coordination of cyanide groups, while the peak of 1.73V belongs to the redox of Mn. The charge and discharge results are consistent with the recorded in-situ CV curves. The intensity of the 1.15V peak slowly decreases from the 4th to the 8th cycle, while the 1.61V peak gradually increases during the cycle.
[0084] In order to analyze the structural and compositional evolution of the KFeMnHCF cathode at different stages of cycling tests and to determine the electrochemical reactions, a series of characterizations, including offline X-ray diffraction (XRD), inductively coupled plasma spectroscopy (ICP-OES), and offline X-ray photoelectron spectroscopy (XPS), were performed. Offline XRD characterization was performed after 100 and 200 cycles of Zn||KFeMnHCF cells assembled with 40% EG PAM@DM hydrogel electrolyte. Fig. 10A As shown in the figure, after 100 cycles, the structure changed, and three new peaks at 20.5°, 27.5°, and 32.5° were confirmed, and the original main peaks weakened. After 200 cycles, these new peaks showed a stronger crystal structure, matching the standard mode of KFeZnHCF, indicating that a complete phase change evolution occurred during the electrochemical process.
[0085] The changes in the chemical composition of the basic elements were further verified by ICP results, thus confirming the structural changes. Fig. 10B The changes in the element contents (K, Fe, Mn, and Zn) of the KFeMnHCF cathode in the original state, after 50 cycles, and after 200 cycles are shown. After 50 cycles, the Zn content in the KFeMnHCF electrode reaches a higher value, indicating that Zn 2+ is the main inserted ion. In contrast, the content of Mn element decreases rapidly after 50 cycles until it is close to 0 after 200 cycles, further indicating that the phase transformation is complete.
[0086] The XPS spectrum of Mn2p shows obvious structural evolution of the cathode. The XPS spectrum of Mn2p shows obvious structural evolution of the cathode. Fig. 10C As shown in Figure 2, in the original cathode, the Mn2p signal can be easily detected. However, after 50, 100, and 150 cycles, the Mn2p signal completely disappears, indicating that the Mn element dissolves rapidly during the cycling process.
[0087] In order to explore the changes of multiple redox sites during the high voltage scanning process, the XPS spectra of C1s were recorded, such as Fig. 10D The results show that the peak shifts significantly toward lower binding energy, indicating that the interaction of low-spin Fe (carbon of cyano group) is weaker. This can be explained by relaxing the electrostatic restraint of carbon on low-spin Fe, resulting in more Fe redox sites being activated.
[0088] The electrochemical performance was recorded by assembling a Zn||Zn symmetric cell using a 40% EG PAM@DM hydrogel electrolyte, which illustrates that a highly reversible anode is also a key factor in achieving a long life of Zn||KFeMnHCF cells. -2 and an area capacity of 0.2 mAh cm -2 The Zn||Zn symmetric battery and Zn|| KFeMnHC The cycle performance of the battery. The voltage-time curve of the pouch cell is recorded at this current density. Fig.11A As shown, the Zn||Zn symmetric battery is -2 and 0.2 mAh cm -2 The current density of 10000 Å / min exhibited a cycle life of more than 1400 h. In addition, no obvious dendrite formation was observed during the cycling process. In contrast, when using 40% EG solution electrolyte, the corrosion and dendrite formation of the Zn anode were significantly more severe, resulting in a greatly reduced life of the symmetric cell to less than 80 h ( Fig. 11B ). This result reveals that the hydrogel developed in the present invention can also stabilize the Zn anode.
[0089] Example 6
[0090] Cyclic performance test results
[0091] In this example, the cycling performance of pouch cells assembled with a series of hydroxyl-rich hydrogel electrolytes was investigated. The results show that neither too little nor too much EG content can well support the stable operation of aqueous Zn||KFeMnHCF batteries. Specifically, the PAM@DM battery with 0% EG exhibits a low cycling efficiency (CE) ( Fig. 12A ). With the increase of EG content, Zn||KFeMnHCF batteries assembled using hydroxyl-rich hydrogel electrolytes show better electrochemical performance ( Figures 12B-12C However, the 60% EG PAM@DM battery showed rapid capacity decay due to the relatively slow electrochemical reaction kinetics ( Fig.12D ).
[0092] According to the above results, the PAM@DM battery with 40% EG provides the best electrochemical performance ( Fig.13A Figure 12). The specific capacity of the Zn||KFeMnHCF battery based on 40% EG PAM@DM reaches about 180 mAh g in the first cycle. -1 , indicating a high utilization efficiency of the iron active sites and manganese redox sites. However, the capacity rapidly dropped to about 100 mAh g due to the inability of zinc ions to reversibly insert into the lattice structure (Jiang-Taylor effect). -1 Once the phase change is complete, the remaining cycle is stable for 10,000 cycles ( Fig.13A ). When the current density increases to 2.66A g -1 40% EG PAM@DM cells showed similar results and could operate stably for 14,500-15,000 cycles ( Figures 13B-13C ). This result proves that the cathode structure remains very stable even during the rapid insertion and extraction of zinc ions.
[0093] Reference Fig.14A Compared with the existing PBAs, the battery prepared by the present invention has excellent overall electrochemical performance, especially a long service life of up to 14,500 cycles and a battery capacity of about 100 mAh g -1 The high capacity and high discharge platform of about 1.7 V are superior to all Zn||PBA batteries reported so far.
[0094] Inspired by the full activation of low-spin Fe and the rapid phase transition (from KFeMnHCF to KFeZnHCF), the present invention further explores the rate performance. In order to reduce the impact of the Chiang-Taylor effect on the structural changes of the battery in the initial stage, the rate performance is recorded after the initial activation process. Fig. 14B The battery showed excellent rate performance at current densities of 1.87 to 3.74 Ag. -1 Between 97-126mAh g -1 Even at a very high current density of 3.74A g -1 A high capacity retention rate of 77% was also achieved under the condition of 1.87Ag -1 When the capacity is fully restored to 126 mAh g -1 .
[0095] Fig. 14C The GCD curve in Figure 2 shows a stable voltage platform at about 1.7 V, indicating excellent rate performance. In addition, after the rate test, the battery can continue to operate stably for 7000 cycles ( Fig.15 Even in the smaller current density range (1.33 to 2.50Ag -1 ), the 40% EG PAM@DM battery still exhibits excellent rate capability in terms of discharge specific capacity and voltage platform ( Fig.16 ).
[0096] Compared with other reported PBA anodes, Zn||KFeMnHCF batteries show higher performance in terms of energy density and power density (based on cathode materials) ( Fig.17 ) 1-7 The use of high-load cathode materials and maintaining good cycle performance when the battery is operated at a lower current density are still challenges in the field of battery applications. Fig.18 It was demonstrated that the KFeMnHCF loading was as high as 26 mg cm -2 The battery cycle performance is 3mAcm -2 Down to 1.8 mAh cm -2 The prepared 40% EG PAM@DM battery exhibits excellent electrochemical performance at very low current density ( Figures 19A-19B ). At 0.3A g -1 The battery provides up to 160mAh g -1 The high specific capacity is still maintained at 100 mAh g after 400 cycles. -1 In addition, at extremely low current density (0.04A g -1 , 0.3 mA cm -2 ) and 8 mg cm -2 At high cathode loading mass, the 40% EG PAM@DM battery still shows an excellent discharge platform of 1.9 V and 1.2 mAh cm -2 The area capacity ( Figures 19C-19D ).
[0097] In order to fully understand the mechanism of the long life of the battery based on 40% EG PAM@DM, its adhesion performance was studied. The results showed that even under a strong shear strength of 1.092 KPa, the two glass bottles were still tightly bonded together ( Fig. 20A ). Fig. 20B Schematic diagram showing the adhesion state of the hydroxyl-rich hydrogel electrolyte on the substrate. The presence of a large number of hydroxyl groups is believed to be the reason for its excellent adhesion performance, which can prevent the KFeMnHCF particles from falling off during cycling. In addition, the entangled polymer chains on the anode surface reduce the contact area between the anode and the solvent molecules, so the hydroxyl-rich hydrogel electrolyte inhibits the dissolution of the KFeMnHCF cathode material, which is one of the reasons for the long life of the 40% EG PAM@DM battery.
[0098] Reference Fig.13A , observed under visible light, after 50 cycles, in the 40% EG PAM@DM battery, the KFeMnHCF particles still fit tightly between the titanium mesh holes, indicating that the cathode has an exceptional stability during the cycling process. In contrast, in the 40% EG solution battery after 50 cycles, the KFeMnHCF particles separated from the cathode surface, causing the cathode surface to appear green ( Fig.21A ). ICP test results further confirmed that 40% EG PAM@DM successfully inhibited the dissolution of KFeMnHCF particles. As evidence to support this finding, Fig. 21B It is shown that after 50 cycles of the 40% EG PAM@DM battery, the Fe and Mn element contents detected in the hydrogel electrolyte remain consistent with the initial state. This indicates that there is no dissolution of the KFeMnHCF material during the electrochemical reaction. In contrast, Fig. 21C It was shown that after 50 cycles of 40% EG solution batteries, a large amount of Fe and Mn elements were detected in the solution electrolyte. Fig.21D The crystal structure of KFeMnHCF at different charge and discharge states after 50 cycles of 40% EG solution battery is shown. The messy XPD peaks indicate structural collapse and damage. This is mainly due to the poor desolvation ability of zinc ions in the 40% EG solution electrolyte. In contrast, the 40% EG PAM@DM battery exhibits strong desolvation ability. After 50 cycles, the crystal structure at different charge and discharge states shows reversible changes, such as Fig.21E The strong desolvation ability of 40% EG PAM@DM hydrogel electrolyte was further confirmed by Raman spectroscopy ( Fig.21F). After 50 cycles, the characteristic peaks of the anode are consistent with the initial state, indicating that the KFeMnHCF cathode has good structural stability during the cycle. However, when the 40% EG solution battery runs for 50 cycles, the characteristic Raman peaks almost disappear, verifying the structural collapse of the KFeMnHCF material due to poor desolvation ability.
[0099] In addition, the 40% EG PAM@DM battery exhibits excellent performance over a wide temperature range ( Fig.22A For example, the 40% EG PAM@DM battery exhibits a long life of more than 5000 cycles at 50°C ( Figure 22G ), indicating that it has excellent electrochemical performance in a wide temperature range. Fig. 22B , the PAM hydrogel electrolyte completely freezes at a temperature of -20 °C, but the 40% EG PAM@DM hydrogel electrolyte does not. Fig. 22C The results show that over a period of 7 days, the 40% EG PAM@DM hydrogel loses water content more slowly compared to the PAM hydrogel that loses water rapidly after only 1 day. These results indicate that the 40% EG PAM@DM hydrogel electrolyte has strong stability under various environments. Figures 22D-22F The charge and discharge curves of the 40% EG PAM@DM battery at 50°C, 25°C, and -20°C were further recorded, achieving stable operation and a charge / discharge rate of about 100 mAh g -1 The specific capacity
[0100] In summary, the present invention utilizes low-cost and hydroxyl-rich hydrogel electrolytes to assemble aqueous Zn / K batteries based on Prussian blue analog (PBA) cathodes by expanding the electrochemical window. These cells exhibit excellent electrochemical performance: ultra-long life of 14,500 cycles, high specific capacity of about 100 mAh / g at high rates, large areal capacity of about 1.8 mAh / cm2, and a high discharge plateau of 1.7-1.9 V. These results can be attributed to three characteristics of the hydroxyl-rich hydrogel electrolyte: (1) high voltage scanning capability based on the expanded electrochemical window, activating more KFeMnHCF reaction sites; (2) complete phase transformation of KFeMnHCF in the hydroxyl-rich hydrogel electrolyte, maintaining a stable crystal structure; (3) due to the large number of -OH groups, the hydrogel electrolyte has strong adhesion, preventing the cathode material from falling off / dissolving, while facilitating the desolvation of metal ions, achieving highly reversible intercalation / deintercalation reactions during long cycles.
[0101] definition
[0102] Throughout the specification, unless otherwise specified, the term "comprise" or variations such as "include" or "contain" will be understood to include a specified integer or integers, but not to exclude the inclusion of any other integers or groups of integers. It should also be noted that in this disclosure, especially in the claims or during, or the terms "comprise" or "include" or "contain" have the meanings given to it in the U.S. patent law. For example, they allow for undefined elements of the description, but exclude elements found in the prior art or affecting the basic or novel characteristics of the invention.
[0103] Furthermore, throughout the specification and claims, unless required otherwise, the term "comprise" or variations thereof, will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integers or groups of integers.
[0104] As used herein, the terms "substantially," "essentially," "approximately," and "about" are used to describe and explain a small change. When used in conjunction with an event or circumstance, the terms may refer to the situation where the event or circumstance occurs exactly, as well as the situation where the event or circumstance occurs approximately. For example, when used in conjunction with a numerical value, these terms may include a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%.
[0105] When the description refers to "one embodiment", "embodiment", "example embodiment" and the like, it means that the described embodiment may include specific features, structures or characteristics, but each embodiment may not necessarily include specific features, and these features do not necessarily refer to the same embodiment. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it is considered that it is within the knowledge of those skilled in the art, and these features, structures or characteristics can be combined with other embodiments to function, whether or not explicitly described.
[0106] In the preparation methods described herein, the steps may be performed in any order without departing from the principles of the invention unless a time sequence or an operational order is explicitly described. In a claim, it should be stated that one step is performed first and then several other steps are performed, which means that the first step is performed before any other steps, but the other steps may be performed in any appropriate order unless the sequence is further listed in the other steps. For example, a claim element listing "step A, step B, step C, step D, and step E" should be understood as step A being performed first and step E being performed last, and steps B, C, and D may be performed in any order between steps A and E, and the order is still within the literal scope of the claim process. A given step or subset of steps may also be repeated.
[0107] The term "Prussian blue analogue" as used herein refers to a crystal structure formed by the combination of a metal ion (usually a transition metal ion) and a cyanide ion, represented by: K x Fe y Mn 1-y [Fe(CN)6] w ·zH2O, where 0 <x,y,w<1,z> 0. Prussian blue analogs have a wide range of applications in the fields of chemistry and materials science. They are often used as catalysts, electrode materials, battery materials, molecular magnets, etc. Due to their unique electrochemical and optical properties, Prussian blue analogs are also used in energy storage and conversion devices such as batteries, electrolytic cells and photovoltaic cells. In addition, Prussian blue analogs also have the ability to adsorb and adsorb and release certain ions and molecules.
[0108] The term "OS PAM@DM hydrogel electrolyte" used in this article refers to a specific type of hydrogel electrolyte that contains an organic solvent (OS), polyacrylamide (PAM) and D(+)-glucose monohydrate (DM). Organic solvents are salts used to dissolve ions and provide conductivity. PAM is a high molecular polymer with the properties of a hydrogel. It can absorb a large amount of water to form a gel state while maintaining a certain mechanical strength and stability. This hydrogel electrolyte may be used in battery systems as an intermediate layer of the battery, separating the anode and cathode while providing ion conduction channels and high mechanical stability.
[0109] Several embodiments and detailed features of the present disclosure are briefly described above. The embodiments described in the present disclosure can be easily used as the basis for designing or modifying other processes and structures to achieve the same or similar goals and / or obtain the same or similar advantages introduced in the embodiments of the present disclosure. Such equivalent structures do not depart from the spirit and scope of the present disclosure, and various changes, substitutions and modifications can be made without departing from the spirit and scope of the present invention.
[0110] References 1.Yang,Q.,Mo,F.,Liu,Z.,Ma,L.,Li,X.,Fang,D.,Chen,S.,Zhang,S.,Zhi,C.,Activating C-coordinated iron of iron hexacyanoferrate for Zn hybrid-ionbatteries with 10 000-cycle lifespan andsuperior ratecapability.Adv.Mater.2019,31,1901521. 2.Wang,D.,Li,C.,Li,Q.,Li,H.,Rehman,J.,Zhi,C,Zhu,L.,Unraveling thehigh energy efficiencyfor Zn||metal hexacyanoferrate batteries in a zinc-potassium hybrid configuration,Nano Energy,104,2022,107990. 3.Deng,W.,Li,Z.,Ye,Y.,Zhou,Z.,Li,Y.,Zhang,M.,Yuan,X.,Hu,J.,Zhao,W.,Huang,Z.,Li,C.,Chen,H.,Zheng,J.,Li,R.,Zn 2+ induced phase transformation ofK2MnFe(CN)6boosts highly stablezinc-ion storage.Adv.Energy Mater.2021,11,2003639. 4.Lu,K.,Song,B.,Zhang,J.,Ma,H.,A rechargeable Na-Zn hybrid aqueousbattery fabricated withnickel hexacyanoferrate and nanostructured zinc,J.Power Sources,2016,321,257-263. 5.Lu,K.,Song,B.,Zhang,Y.,Ma,H.,Zhang,J.,Encapsulation of zinchexacyanoferrate nanocubeswith manganese oxide nanosheets for high-performance rechargeable zinc ion batteries.J.Mater.Chem.A,2017,5,23628-23633. 6.Jia,Z.,Wang,B.,Wang,Y.,Copper hexacyanoferrate with a well-definedopen framework as apositive electrode for aqueous zinc ion batteries,Mater.Chem.Phys.2015,149-150,601-606. 7.Wang,L.,Wang,P.,Wang,T.,Yin,Y.,Guo,Y.,Wang,C.,Prussian bluenanocubes as cathodematerials for aqueous Na-Zn hybrid batteries,J.PowerSources,2017,355,18-22.
Claims
1. A water-soluble zinc-based battery having a hydroxyl-rich hydrogel electrolyte, characterized in that: The water-soluble zinc-based battery comprises: A cathode having a current collector and at least one active material, the at least One active material is K x Fe y Mn 1-y [Fe(CN)6] w ·zH2O, where 0 <x,y,w<1,z> 0; an anode; and A hydroxyl-rich hydrogel electrolyte provides a channel for ion conduction between the cathode and the anode, wherein the hydrogel electrolyte comprises a salt solution electrolyte, at least one organic solvent, polyacrylamide and D(+)-glucose monohydrate. The current density is between 1.0A -1 Up to 4.0A g -1 The water-soluble zinc-based battery with the hydroxyl-rich hydrogel electrolyte can stably operate for at least 10,000 cycles at 0.2 mA cm -2 and an area capacity of 0.2 mAh cm -2 It has a cycle life of more than 1400 hours under the conditions of , and achieves a high capacity retention rate of at least 75%.
2. The water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte according to claim 1, wherein the water-soluble zinc-based battery further comprises a separator between the cathode and the anode.
3. The water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte according to claim 1, wherein the material of the anode comprises a zinc plate or a zinc foil.
4. The water-soluble zinc-based battery with hydroxyl-rich hydrogel electrolyte according to claim 1, wherein the current collector comprises carbon cloth, carbon paper, graphite paper, titanium foil / mesh, or stainless steel.
5. A water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte according to claim 1, wherein the volume percentage of the at least one organic solvent is between 0.1% and 70%, and wherein the organic solvent comprises one or more selected from methanol, ethanol, ethylene glycol, glycerol and butene tetraol.
6. The water-soluble zinc-based battery with hydroxyl-rich hydrogel electrolyte according to claim 1, wherein the cathode further comprises one or more conductive particles and at least one binder.
7. The water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte according to claim 1, wherein the one or more conductive particles include conductive carbon black, Ketjen black, and the binder includes polyvinylidene fluoride, polytetrafluoroethylene.
8. The water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte according to claim 1, wherein the salt solution electrolyte comprises a potassium salt and a zinc salt, the potassium salt being selected from one or more of potassium bis(trifluoromethanesulfonyl)imide, potassium trifluoromethanesulfonate, potassium perchlorate, potassium borofluoride, potassium chloride, and potassium sulfate, and the zinc salt being selected from one or more of zinc trifluoromethanesulfonylimide, zinc trifluoromethanesulfonate, zinc perchlorate, zinc borofluoride, zinc chloride, and zinc sulfate.
9. The water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte according to claim 1, wherein the hydroxyl-rich hydrogel electrolyte is prepared by the following method: preparing the salt solution electrolyte at normal temperature and pressure; mixing the organic solvent with the salt solution electrolyte to form a first mixed solution; Dissolving the polyacrylamide, the D(+)-glucose monohydrate and a photoinitiator in the first mixed solution to form a second mixed solution, wherein the molar ratio of the polyacrylamide to the D(+)-glucose monohydrate is 7:1; The second mixed solution is transferred into a mold and exposed to UV for reaction and an inert gas is bubbled through the second mixed solution to remove oxygen, thereby forming a hydrogel electrolyte having rich hydroxyl groups.
10. The water-soluble zinc-based battery with hydroxyl-rich hydrogel electrolyte according to claim 9, wherein the inert gas comprises nitrogen and argon.
11. The water-soluble zinc-based battery with a hydroxyl-rich hydrogel electrolyte according to claim 9, wherein the time of reaction under UV exposure is 30 to 180 minutes.
Citation Information
Cited By
Hydrogel electrolyte, aqueous zinc-based battery and preparation method of aqueous zinc-based battery
CN120767443A
